La idea de un cuasi pensamiento de segundo-orden: Una objección a la teoría reflexiva del pensamiento consciente - Vidal, Javier (2005)
The thesis defended in this paper is that the Higher-Order Thought Theory is actually inconsistent. According to the theory it would be possible to introduce the notion of a second-order quasi-thought from S. Shoemaker’s notion of a quasi-memory. On the one hand, a secondorder quasi-thought, but not necessarily a quasi-memory, entails an use of ‘I’ as subject. On the other hand, Shoemaker conceives the use of ‘I’ as subject in terms of the notion of an immunity to error through misidentification. Now, as the notion of a quasi-memory as the notion of a second-order quasi-thought are liable to allow for the cases of personal and psychological fission where the causal series between events belonging to one and the same subject is broken, and thus there is not an immunity to error through misidentification. Then, the notion of a second-order quasi-thought would allow for cases where an use of ‘I’ as subject is not immune to error through misidentification!